JVP Data Set 2001 & 2004 - Warwick, Travis; Wixson, Emily; Rouse, Ken (My University, 2005)
The Journal Value Project created a database of cost and valuation data for journals in all areas of the sciences and social sciences.
Utilizing Henry ("Heinz") Barschall's method of approximating the number of characters in a given volume of a Journal, the project collected character count data for 2142 academic journals for the years 2001 and 2004. By dividing the number of characters per page by the journal's cost and again by the ISI Impact Factor, an index is created which can be used to compare the relative value of similar journals. This index is referred to as the Barschall Factor.
Keywords: Journal Evaluation